Black Athena : the Afroasiatic roots of classical civilization. - Bernal, Martin (Rutgers University Press, 2020)
What is classical about Classical civilization? In one of the most audacious works of scholarship ever written, Martin Bernal challenges the foundation of our thinking about this question. Classical civilization, he argues, has deep roots in Afroasiatic cultures. But these Afroasiatic influences have been systematically ignored, denied or suppressed since the eighteenth century--chiefly for racist reasons. The popular view is that Greek civilization was the result of the conquest of a sophisticated but weak native population by vigorous Indo-European speakers--Aryans--from the North. But the Classical Greeks, Bernal argues, knew nothing of this "Aryan model." They did not see their institutions as original, but as derived from the East and from Egypt in particular. In an unprecedented tour de force, Bernal links a wide range of areas and disciplines--drama, poetry, myth, theological controversy, esoteric religion, philosophy, biography, language, historical narrative, and the emergence of "modern scholarship."